(untitled) (Proceedings of The National Conference on Community Engagement, 2026)
—This Community Service Program (Kuliah Kerja Nyata/KKN) aims to analyze and provide assistance in marketing strategies for salted egg micro, small, and medium enterprises (MSMEs) in Ngletih Village, Kediri City. Salted egg MSMEs have considerable local economic potential; however, they face several marketing challenges, including limited market reach, simple product packaging, and the underutilization of digital marketing platforms. The methods employed in this program include field observation, interviews with MSME owners, and direct assistance in developing marketing strategies. The assistance activities involve improving product packaging, introducing digital marketing through social media, and preparing simple promotional materials. The results indicate that marketing strategy assistance enhances MSME owners’ understanding of the importance of planned and adaptive marketing strategies in response to technological developments. Furthermore, an increase in consumer interest and market reach was observed after the implementation of marketing optimization efforts. This program is expected to strengthen the competitiveness of MSMEs and support sustainable local economic development in Ngletih Village.